(untitled) (Research, Society and Development, 2022)
The term “bionegócios” is based on the sustainable use of natural resources and the recognition of the rights of traditional communities. From this definition, biobusiness can encompass simple processing processes, activities with economic use of the cultural value of biodiversity, and even chemical and/or biological processes of greater complexity, requiring specific knowledge for product development. The objective of this work was to carry out a bibliometric analysis of the term biobusiness, where the authors with the greatest contribution that encompass the theme are presented, as well as the countries that publish this theme. Based on the Scopus database, four fields were considered regarding the publications of “bionegócios”, based on a keyword search of its English form, biobusiness. The bibliometric data obtained were exported to the VOSviewer software, where bibliometric networks were built to support this analysis. The scientific production related to the biobusiness theme delimited articles with a maximum of 20 authors per paper, from which 1,116 authors were observed in the mentioned database, where the most cited authors have published the longest. Besides this, the scientific contribution per country was observed, as well as the citation relations between them, and that from these relations it was possible to delineate three groups of countries, with relations centered and based especially on US researchers. The bibliometric network was also traced taking into perspective the Brazilian research with the aforementioned keyword, presenting a recent scenario of scientific production for the country, related to the growing university-industry interaction and its great power of contribution to research in biobusiness.